Uptake of the Fusarium Effector Avr2 by Tomato Is Not a Cell Autonomous Event - Di, Xiaotang; Gomila, Jo; Ma, Lisong; van den Burg, Harrold A.; Takken, Frank L. W. (Frontiers in Plant Science, 2016)
Pathogens secrete effector proteins to manipulate the host for their own proliferation. Currently it is unclear whether the uptake of effector proteins from extracellular spaces is a host autonomous process. We study this process using the Avr2 effector protein from Fusarium oxysporum f.sp. lycopersici (Fol). Avr2 is an important virulence factor that is secreted into the xylem sap of tomato following infection. Besides that, it is also an avirulence factor triggering immune responses in plants carrying the I-2 resistance gene. Recognition of Avr2 by I-2 occurs inside the plant nucleus. Here we show that pathogenicity of an Avr2 knockout Fusarium (FolΔAvr2) strain is fully complemented on transgenic tomato lines that express either a secreted (Avr2) or cytosolic Avr2 (ΔspAvr2) protein, indicating that Avr2 exerts its virulence functions inside the host cells. Furthermore, our data imply that secreted Avr2 is taken up from the extracellular spaces. Grafting studies were performed in which scions of I-2 tomato plants were grafted onto either a ΔspAvr2 or on an Avr2 rootstock. Although the Avr2 protein could readily be detected in the xylem sap of the grafted plant tissues, no I-2-mediated immune responses were induced suggesting that I-2-expressing tomato cells cannot autonomously take up the effector protein from the xylem sap. Additionally, ΔspAvr2 and Avr2 plants were crossed with I-2 plants. Whereas ΔspAvr2/I-2 F1 plants showed a constitutive immune response, immunity was not triggered in the Avr2/I-2 plants confirming that Avr2 is not autonomously taken up from the extracellular spaces to trigger I-2. Intriguingly, infiltration of Agrobacterium tumefaciens in leaves of Avr2/I-2 plants triggered I-2 mediated cell death, which indicates that Agrobacterium triggers effector uptake. To test whether, besides Fol, effector uptake could also be induced by other fungal pathogens the ΔspAvr2 and Avr2 transgenic lines were inoculated with Verticillium dahliae. Whereas ΔspAvr2 plants became hyper-susceptible to infection, no difference in disease development was found in the Avr2 plants as compared to wild-type plants. These data suggest that effector uptake is not a host autonomous process and that Fol and A. tumefaciens, but not V. dahliae, facilitate Avr2 uptake by tomato cells from extracellular spaces.